Analisis Kemampuan Literasi Informasi Siswa SMP dalam Menghadapi Pembelajaran di Era Society 5.0 - Salsabila, Ainus; Hidayati, Siti Nurul; Aulia, Ernita Vika (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to analyze the information literacy abilities of eighth-grade students at Pademawu 1 State Junior High School in the context of learning science in the era of Society 5.0. The researchers also examine each indicator used to measure information literacy skills to provide insights for educators on how to improve these skills in the future.Method – The study employs a survey design, which is analyzed quantitatively and descriptively. It focuses on the information literacy skills of junior high school students and the role of education in preparing them for Society 5.0. The data is supported by a literature review that includes relevant research and other supporting sources.Findings – The results show that students' information literacy skills are generally good. However, there are deficiencies in the indicators for assessing and analyzing information, and the use of information is rated as only sufficient. This is because the activity of analyzing information requires high-level thinking skills/critical thinking, but school questions tend to train memory skills, leading to underdeveloped critical thinking skills. Additionally, internal, and external factors also influence this low ability. The ability to use information is low because learning is still teacher-centered, with students being less active in the learning process. A potential solution is to employ learning methods that develop high-level skills and are student-centered. Research Implications – This research can help educators understand the analysis of students' information literacy abilities. However, the study has not been empirically tested, so further research is needed to determine effective strategies to improve information literacy skills, such as appropriate learning methods, to enhance overall literacy skills.